WANITA KARIER PERSPEKTIF HUKUM ISLAM - Aulia Ranny Priyatna (Center of Gender Studies and Child of State Islamic Institute of Metro, 2019)
Career women are women who pursue and love something or several jobs in full in a relatively long time to achieve something progress in life, work or position. In general, careers are pursued by women who take part in the public sector. In addition, to have a career means having to pursue certain professions that require abilities, capacities and expertise. Islam does not forbid a career woman, the most important thing is how she meets the conditions or conditions that allow her to become a career woman, which must be accompanied by the rules set by Islam between her husband's consent, balancing the demands of the household and the demands of work, her work does not cause khalwat , avoid work that is not in accordance with the psychological character of women, and stay away from all sources of defamation.Q, S. An-Nisaa: 32 clearly states that men and women have the same rights to try and the right to obtain what each is trying for. Thus men and women each have a role in life that can bring them together in a big task, namely building a society and carrying the burden of development without disparaging one type or another, or spreading animosity between the two.